L’assurance de responsabilité professionnelle : les obligations de l’assuré en cas de sinistre - Dumais, Christian N. (Assurances, 1984)
Mr. Dumais considers the importance of advising insurers of possible professional liability insurance claims. The policy is quite precise on this question: if the insured does not wish to lose his rights of indemnity, he must advise his broker, who in turn will give notice to the insurer of the possibility or probability of a claim. It is not up to the insured to judge whether notice is necessary or not. If there is the least doubt, he must inform his broker, who will act on his behalf to give details to the insurer.